2020
DOI: 10.1155/2020/7802103
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fly Ash and Slag Generated by Incineration of Municipal Solid Waste in Concrete

Abstract: As landfill space for the disposal of products of municipal solid waste incineration (MSWI) such as fly ash and slag becomes increasingly scarce, a reduction of disposed material is urgently required. The method of using incineration products in concrete production is explored in this paper through a feasibility study of utilizing fly ash and slag to replace cement and coarse aggregate in appropriate proportions. Results show that C30 concrete optimum replacement rates of fly ash and slag are 30% and 20%, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Both being volatile in nature, a major amount of Hg and Cd are eliminated from the coal at the time of combustion in the furnace. Moreover, it has been found that smaller the size of fly ash particles higher will be the concentration of heavy metals on their surface i.e., larger fly ash particles will have lesser amount of heavy metals and other elements on their surface than the small-sized fly ash particles [69,70]. In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71].…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…Both being volatile in nature, a major amount of Hg and Cd are eliminated from the coal at the time of combustion in the furnace. Moreover, it has been found that smaller the size of fly ash particles higher will be the concentration of heavy metals on their surface i.e., larger fly ash particles will have lesser amount of heavy metals and other elements on their surface than the small-sized fly ash particles [69,70]. In a thermal power plant, there are two types of ashes; bottom ash and fly ash [71].…”
Section: Inductively Coupled Plasma Analysis Of Fly Ash Digested Samplementioning
confidence: 99%
“…The first stage of the valorisation process is initial seasoning to dehydrate and stabilise the slag. Then, appropriate size fractions and ferrous and non-ferrous metals are separated using a magnetic and induction separator [ 22 , 23 ]. Figure 3 presents the tested slags in the raw state (a1,b1) and after mechanical treatment (a2,b2).…”
Section: Methodsmentioning
confidence: 99%
“…The studied MSWI ashes exhibit a high concentration of chlorides and sulfates, which is an unfavourable feature for a potential concrete additive [ 21 , 22 ]. Publication [ 23 ] indicated that the MSWI slag structure is loose and irregular, and its main component is SiO 2 . The SiO 2 and Al 2 O 3 in fly ash and slag participate in the hydration reaction of cement and can increase concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…The coal fly ash is used in the concrete production process in China. Zeng has found the optimum substitution level in concert production as ash substitution level to be 30% and the slag substitution level to be 20% [83]. According his research the strength of concrete mixed with certain amount of coal fly ash was not diminished.…”
Section: Examples Of Effective Cfa Recyclingmentioning
confidence: 99%
“…Berndt pointed out that we can spot the benefits of partial cement replacement with recycled coal fly ash. This is not only economically beneficial, but is also a very important factor towards the promotion of sustainable concrete production [83].…”
Section: Examples Of Effective Cfa Recyclingmentioning
confidence: 99%